STRATEGI BRANDING PADA MADAYA COFFEE SEBAGAI SARANA PENINGKATAN PENJUALAN - Zahra Kaltsum (2023)
Dompet Dhuafa which presents Madaya Coffee at the end of 2019 by utilizing coffee farmers made by Dompet Dhuafa as partners. This study aims to examine the branding strategy carried out by Madaya Coffee as a means of increasing its sales by using the brand strategy doctrine theory. The method used is qualitatively descriptive by using primary data sources and secondary data. The author uses the Filling System data analysis technique introduced by Wimmer and Dominick. The data that the authors obtained in conducting the research were analyzed by creating categories based on five stages of the brand strategy doctrine theory, and then validating the data by triangulating techniques, sources and time. The final result of this study shows that from the five existing stages, Madaya Coffee has only made optimal efforts at the Brand Advantage stage. Seeing that there are still many aspects that Madaya Coffee has not done optimally. This is proven from the research results obtained that currently Madaya Coffee is still focused on products for sales purposes, which is seen from sales data obtained that Madaya Coffee's sales figures are not at good results (did not reach the target). Meanwhile, the branding process itself certainly includes many things, not only on products, but also on all continuous aspects to produce Madaya Coffee branding to customers according to the identity they want to show and convey. Keywords: brand doctrine theory, branding strategy, madaya coffee, sales